Kajian Bahasa Arab dari A Historis hingga Historis - Wati Susiawati (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2019)
Language is essentially the sound, which is in the form of waves of air coming out of the lungs through sound pipes and across speech organs or sound devices. Arabic, as one of the Semitic languages, has special features in sound aspects that no other language has. Arabic is a language that has unique characteristics and is different from other languages in the world. The characteristics and uniqueness of the Arabic language between them is the language of derivation (ishtiqâq), rich in sound, language that is rich in form (ṣîghah), language of taṣrîf, i’râb, a language rich in expressions, various kinds of sentence techniques, languages that are rich in syntax (naḥw) and others.